Fossil hominin radii from the Sima de los Huesos Middle Pleistocene site (Sierra de Atapuerca, Spain). Issue 90 (January 2016) - Rodríguez, Laura; Carretero, José Miguel; García-González, Rebeca; Lorenzo, Carlos; Gómez-Olivencia, Asier; Quam, Rolf; Martínez, Ignacio; Gracia-Téllez, Ana; Arsuaga, Juan Luis
Abstract: Complete radii in the fossil record preceding recent humans and Neandertals are very scarce. Here we introduce the radial remains recovered from the Sima de los Huesos (SH) site in the Sierra de Atapuerca between 1976 and 2011 and which have been dated in excess of 430 ky (thousands of years) ago. The sample comprises 89 specimens, 49 of which are attributed to adults representing a minimum of seven individuals. All elements are described anatomically and metrically, and compared with other fossil hominins and recent humans in order to examine the phylogenetic polarity of certain radial features. Radial remains from SH have some traits that differentiate them from those of recent humans and make them more similar to Neandertals, including strongly curved shafts, anteroposterior expanded radial heads and both absolutely and relatively long necks. In contrast, the SH sample differs from Neandertals in showing a high overall gracility as well as a high frequency (80%) of an anteriorly oriented radial tuberosity. Thus, like the cranial and dental remains from the SH site, characteristic Neandertal radial morphology is not present fully in the SH radii. We also analyzed the cross-sectional properties of the SH radial sample at two different levels: mid-shaft and at the midpoint of the neck length. When standardized by shaft length, no difference in the mid-shaft cross-sectional properties were found between the SH hominins, Neandertals and recent humans. Nevertheless, due to their long neck length, the SH hominins show a higher lever efficiency than either Neandertals or recent humans. Functionally, the SH radial morphology is consistent with more efficient pronation-supination and flexion-extension movements. The particular trait composition in the SH sample and Neandertals resembles more closely morphology evident in recent human males.